An Analysis on Students’ Motivation in English Reading - Sulaiman Sulaiman (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2019)
The purpose of this research was to know the students’ motivation in English reading. The reason why this research was conducted was to find what the aspect which influences students’ motivation in English reading and the reason behind it. The population of this research was 210 students. The researcher took 136 students as the sample of this research. The sampling technique that researcher used was simple random sampling. Then, 4 students purposively were interviewed by the researcher.  The questionnaire result showed that, because of the high means score in reading curiosity (RC) was 3.30. Then, the mean score for reading involvement (RI) was 3.30. Also, the mean score for importance of reading (IRE) was 3.60, researcher concluded that the students were intrinsically motivated. The interviews result showed that, beside to add knowledge, or learn culture, most of them answered that their motivation was to add new vocabulary. Even though there was still negative attitude like feeling shy or afraid of making mistake, they thought that English reading was beneficial for them like to know other cultures.  In order to promote learners’ intrinsic motivation, one of the best ways might be by providing them with interesting material. The lecturer should provide a wide selection of interesting reading materials and let the students choose and read the book in a comfortable situation.